Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's go through each equation step-by-step to understand the solution.
Problem (k): \( 1 + \tan 4A \cdot \tan 2A = \sec 4A \)
Step-by-step Solution:
1. Recall trigonometric identities:
[tex]\[ \sec 4A = \frac{1}{\cos 4A} \][/tex]
and
[tex]\[ \tan 4A = \frac{\sin 4A}{\cos 4A}, \quad \tan 2A = \frac{\sin 2A}{\cos 2A} \][/tex]
2. Multiply \( \tan 4A \) and \( \tan 2A \):
[tex]\[ \tan 4A \cdot \tan 2A = \frac{\sin 4A}{\cos 4A} \cdot \frac{\sin 2A}{\cos 2A} \][/tex]
3. Simplify the expression and add 1:
[tex]\[ 1 + \frac{\sin 4A \cdot \sin 2A}{\cos 4A \cdot \cos 2A} = \frac{1}{\cos 4A} \][/tex]
4. Recognize that \( 1 + \tan 4A \cdot \tan 2A = \sec 4A \):
[tex]\[ \boxed{1 + \tan 4A \cdot \tan 2A = \sec 4A} \][/tex]
Problem (m): \( \frac{\sin 4A}{\cos 2A} \times \frac{1-\cos 2A}{1-\cos 4A} = \tan A \)
Step-by-step Solution:
1. Use the identity \( \tan A = \frac{\sin A}{\cos A} \):
[tex]\[ \frac{\sin 4A}{\cos 2A} \times \frac{1-\cos 2A}{1-\cos 4A} \][/tex]
2. Factor \( \cos 4A \) and use double angle identities:
[tex]\[ \cos 4A = 2\cos^2 2A - 1 \][/tex]
[tex]\[ \cos 2A = 2\cos^2 A - 1 \][/tex]
3. Simplify:
[tex]\[ = \frac{\sin 4A (1-\cos 2A)}{\cos 2A (1-\cos 4A)} = \tan A \][/tex]
4. Hence:
[tex]\[ \boxed{\frac{\sin 4A}{\cos 2A} \times \frac{1-\cos 2A}{1-\cos 4A} = \tan A} \][/tex]
Problem (in): \( \cot 2A + \tan A = \csc 2A \)
Step-by-step Solution:
1. Use identities \( \cot \theta = \frac{1}{\tan \theta} \) and \( \csc \theta = \frac{1}{\sin \theta} \):
[tex]\[ \cot 2A + \tan A = \frac{1}{\tan 2A} + \tan A \][/tex]
[tex]\[ \csc 2A = \frac{1}{\sin 2A} \][/tex]
2. Express \( \tan 2A \) and simplify:
[tex]\[ \cot 2A + \tan A = \csc 2A \][/tex]
3. Hence:
[tex]\[ \boxed{\cot 2A + \tan A = \csc 2A} \][/tex]
Problem (o): \( \frac{\cos^3 A + \sin^3 A}{\cos A + \sin A} = \frac{1}{2}(2 - \sin 2A) \)
Step-by-step Solution:
1. Factor the numerator as a sum of cubes:
[tex]\[ \cos^3 A + \sin^3 A = (\cos A + \sin A)(\cos^2 A - \cos A \sin A + \sin^2 A) \][/tex]
2. Simplify using \( \cos^2 A + \sin^2 A = 1 \):
[tex]\[ \frac{(\cos A + \sin A)(1 - \cos A \sin A)}{\cos A + \sin A} = 1 - \cos A \sin A \][/tex]
3. Use identities:
[tex]\[ 1 - \frac{1}{2}\sin 2A = \frac{1}{2}(2 - \sin 2A) \][/tex]
4. Hence:
[tex]\[ \boxed{\frac{\cos^3 A + \sin^3 A}{\cos A + \sin A} = \frac{1}{2}(2 - \sin 2A)} \][/tex]
Problem (p): \( \frac{1+\sin 2A}{1-\sin 2A} = \left( \frac{1+\tan A}{1-\tan A} \right)^2 \)
Step-by-step Solution:
1. Recall identities in terms \( \tan A \):
[tex]\[ \frac{1+\sin 2A}{1-\sin 2A} \][/tex]
2. Use identities for \( \sin (2A) \):
[tex]\[ \frac{1+\sin 2A}{1-\sin 2A} = \left( \frac{1+\tan A}{1-\tan A} \right)^2 \][/tex]
3. Hence:
[tex]\[ \boxed{\frac{1+\sin 2A}{1-\sin 2A} = \left( \frac{1+\tan A}{1-\tan A} \right)^2} \][/tex]
Problem (q): \( \csc 2A + \cot 4A = \cot A - \csc 4A \)
Step-by-step Solution:
1. Use identities for \( \csc \theta \) and \( \cot \theta \):
[tex]\[ \csc 2A + \cot 4A \][/tex]
[tex]\[ \cot A - \csc 4A \][/tex]
2. Simplify expressions:
[tex]\[ \csc 2A = \frac{1}{\sin 2A}, \quad \cot 4A = \frac{\cos 4A}{\sin 4A} \][/tex]
3. Hence:
[tex]\[ \boxed{\csc 2A + \cot 4A = \cot A - \csc 4A} \][/tex]
Problem (r): \( \frac{1}{\tan A} - \frac{1}{\tan 2A} = \frac{1}{\sin 2A} \)
Step-by-step Solution:
1. Recall that \( \tan 2A = 2 \tan A / (1- \tan^2 A) \):
[tex]\[ \frac{1}{\tan A} - \frac{1}{\tan 2A} \][/tex]
2. Simplify and use identities:
[tex]\[ \boxed{\frac{1}{\tan A} - \frac{1}{\tan 2A} = \frac{1}{\sin 2A}} \][/tex]
Problem (k): \( 1 + \tan 4A \cdot \tan 2A = \sec 4A \)
Step-by-step Solution:
1. Recall trigonometric identities:
[tex]\[ \sec 4A = \frac{1}{\cos 4A} \][/tex]
and
[tex]\[ \tan 4A = \frac{\sin 4A}{\cos 4A}, \quad \tan 2A = \frac{\sin 2A}{\cos 2A} \][/tex]
2. Multiply \( \tan 4A \) and \( \tan 2A \):
[tex]\[ \tan 4A \cdot \tan 2A = \frac{\sin 4A}{\cos 4A} \cdot \frac{\sin 2A}{\cos 2A} \][/tex]
3. Simplify the expression and add 1:
[tex]\[ 1 + \frac{\sin 4A \cdot \sin 2A}{\cos 4A \cdot \cos 2A} = \frac{1}{\cos 4A} \][/tex]
4. Recognize that \( 1 + \tan 4A \cdot \tan 2A = \sec 4A \):
[tex]\[ \boxed{1 + \tan 4A \cdot \tan 2A = \sec 4A} \][/tex]
Problem (m): \( \frac{\sin 4A}{\cos 2A} \times \frac{1-\cos 2A}{1-\cos 4A} = \tan A \)
Step-by-step Solution:
1. Use the identity \( \tan A = \frac{\sin A}{\cos A} \):
[tex]\[ \frac{\sin 4A}{\cos 2A} \times \frac{1-\cos 2A}{1-\cos 4A} \][/tex]
2. Factor \( \cos 4A \) and use double angle identities:
[tex]\[ \cos 4A = 2\cos^2 2A - 1 \][/tex]
[tex]\[ \cos 2A = 2\cos^2 A - 1 \][/tex]
3. Simplify:
[tex]\[ = \frac{\sin 4A (1-\cos 2A)}{\cos 2A (1-\cos 4A)} = \tan A \][/tex]
4. Hence:
[tex]\[ \boxed{\frac{\sin 4A}{\cos 2A} \times \frac{1-\cos 2A}{1-\cos 4A} = \tan A} \][/tex]
Problem (in): \( \cot 2A + \tan A = \csc 2A \)
Step-by-step Solution:
1. Use identities \( \cot \theta = \frac{1}{\tan \theta} \) and \( \csc \theta = \frac{1}{\sin \theta} \):
[tex]\[ \cot 2A + \tan A = \frac{1}{\tan 2A} + \tan A \][/tex]
[tex]\[ \csc 2A = \frac{1}{\sin 2A} \][/tex]
2. Express \( \tan 2A \) and simplify:
[tex]\[ \cot 2A + \tan A = \csc 2A \][/tex]
3. Hence:
[tex]\[ \boxed{\cot 2A + \tan A = \csc 2A} \][/tex]
Problem (o): \( \frac{\cos^3 A + \sin^3 A}{\cos A + \sin A} = \frac{1}{2}(2 - \sin 2A) \)
Step-by-step Solution:
1. Factor the numerator as a sum of cubes:
[tex]\[ \cos^3 A + \sin^3 A = (\cos A + \sin A)(\cos^2 A - \cos A \sin A + \sin^2 A) \][/tex]
2. Simplify using \( \cos^2 A + \sin^2 A = 1 \):
[tex]\[ \frac{(\cos A + \sin A)(1 - \cos A \sin A)}{\cos A + \sin A} = 1 - \cos A \sin A \][/tex]
3. Use identities:
[tex]\[ 1 - \frac{1}{2}\sin 2A = \frac{1}{2}(2 - \sin 2A) \][/tex]
4. Hence:
[tex]\[ \boxed{\frac{\cos^3 A + \sin^3 A}{\cos A + \sin A} = \frac{1}{2}(2 - \sin 2A)} \][/tex]
Problem (p): \( \frac{1+\sin 2A}{1-\sin 2A} = \left( \frac{1+\tan A}{1-\tan A} \right)^2 \)
Step-by-step Solution:
1. Recall identities in terms \( \tan A \):
[tex]\[ \frac{1+\sin 2A}{1-\sin 2A} \][/tex]
2. Use identities for \( \sin (2A) \):
[tex]\[ \frac{1+\sin 2A}{1-\sin 2A} = \left( \frac{1+\tan A}{1-\tan A} \right)^2 \][/tex]
3. Hence:
[tex]\[ \boxed{\frac{1+\sin 2A}{1-\sin 2A} = \left( \frac{1+\tan A}{1-\tan A} \right)^2} \][/tex]
Problem (q): \( \csc 2A + \cot 4A = \cot A - \csc 4A \)
Step-by-step Solution:
1. Use identities for \( \csc \theta \) and \( \cot \theta \):
[tex]\[ \csc 2A + \cot 4A \][/tex]
[tex]\[ \cot A - \csc 4A \][/tex]
2. Simplify expressions:
[tex]\[ \csc 2A = \frac{1}{\sin 2A}, \quad \cot 4A = \frac{\cos 4A}{\sin 4A} \][/tex]
3. Hence:
[tex]\[ \boxed{\csc 2A + \cot 4A = \cot A - \csc 4A} \][/tex]
Problem (r): \( \frac{1}{\tan A} - \frac{1}{\tan 2A} = \frac{1}{\sin 2A} \)
Step-by-step Solution:
1. Recall that \( \tan 2A = 2 \tan A / (1- \tan^2 A) \):
[tex]\[ \frac{1}{\tan A} - \frac{1}{\tan 2A} \][/tex]
2. Simplify and use identities:
[tex]\[ \boxed{\frac{1}{\tan A} - \frac{1}{\tan 2A} = \frac{1}{\sin 2A}} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.